Arthur the king [videorecording (Blu-Ray + DVD)] - Collins, Rob, 1979-; Matley, Kevin; Brandt, Michael, 1968-; Wahlberg, Mark, 1971-; Emmanuel, Nathalie, 1989-; Liu, Simu, 1989-; Landes, Michael; Lindnord, Mikael (Lionsgate, 2024)
Over the course of ten days and 435 miles, an unbreakable bond is forged between pro adventure racer Michael Light and a scrappy street dog companion dubbed Arthur. Based on an incredible true story, ARTHUR THE KING follows Light, desperate for one last chance to win, as he convinces a sponsor to back him and a team of athletes for the Adventure Racing World Championship in the Dominican Republic. As the team is pushed to their outer limits of endurance in the race, Arthur redefines what victory, loyalty and friendship truly mean.